2022
DOI: 10.1002/ptr.7384
|View full text |Cite
|
Sign up to set email alerts
|

Crocin alleviates cognitive impairment associated with atherosclerosis via improving neuroinflammation in LDLR−/− mice fed a high‐fat/cholesterol diet

Abstract: Crocin has been extensively investigated in treating neurodegenerative diseases.However, its effect on cognitive impairment associated with atherosclerosis remains unknown. The present study aimed to explore the potential mechanism of crocin on cognitive impairment in a mouse model of atherosclerosis. LDLR À/À mice fed a highfat/cholesterol diet were administered variable-dose crocin for 56 days through gavage. Biochemical tests showed that serum triglycerides and circulating lipopoly-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…These plants are primarily used in many kinds of cuisines as flavoring and coloring agents as well as in traditional medicines for the treatment of edema, headache, fever, jaundice, and hypertension [ 9 , 10 ]. A number of studies have demonstrated that Crocin has a wide range of activities, including antioxidant [ 11 , 12 ], anti-inflammatory [ 13 , 14 ], anti-cancer [ 15 ], anti-atherosclerotic [ 16 , 17 ], anti-depressant [ 18 ], cardioprotective [ 19 ], and hepatoprotective effects [ 20 ]. Several studies have shown that Crocin inhibits NF-κB activity and suppresses proinflammatory mediators and cytokines [ 14 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These plants are primarily used in many kinds of cuisines as flavoring and coloring agents as well as in traditional medicines for the treatment of edema, headache, fever, jaundice, and hypertension [ 9 , 10 ]. A number of studies have demonstrated that Crocin has a wide range of activities, including antioxidant [ 11 , 12 ], anti-inflammatory [ 13 , 14 ], anti-cancer [ 15 ], anti-atherosclerotic [ 16 , 17 ], anti-depressant [ 18 ], cardioprotective [ 19 ], and hepatoprotective effects [ 20 ]. Several studies have shown that Crocin inhibits NF-κB activity and suppresses proinflammatory mediators and cytokines [ 14 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The included trials suggest that saffron administration is well tolerance with few adverse events, whereas conventional drugs for AD, depression, ADHD, or OCD appear to have varying degrees of side effects, such as headache, constipation, tremor, insomnia, and decreased appetite. (Cerda-Bernad et al, 2022;D'Onofrio et al, 2021;Saeedi & Rashidy-Pour, 2021;Song et al, 2022;Sugiura et al, 2022;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven included studies, one study evaluated the effects of saffron (60 mg) in combination with sedge and honey in patients with major neurocognitive disorders compared with routine anti‐MCD medications (Akouchekian et al, 2018), one study reported the effects of crocin in patients under methadone maintenance treatment (Abbaszadeh‐Mashkani et al, 2020), and the remaining studies examined the effects of saffron alone in patients with mild cognitive impairment or AD compared with placebo or anti‐AD medications. The possible mechanisms underlying the effects of saffron in improving cognitive disorders is related to its inhibitory action on acetylcholinesterase activity, aggregation of beta‐amyloid protein into amyloid plaques and tau protein into neurofibrillary tangles, partly through its antioxidant, anti‐inflammatory, and antiapoptotic abilities (Cerda‐Bernad et al, 2022; D'Onofrio et al, 2021; Saeedi & Rashidy‐Pour, 2021; Song et al, 2022; Sugiura et al, 2022; Wang et al, 2019). In addition, saffron may enhance memory and learning functions by decreasing glucose and improving insulin resistance (Sanaie et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of crocin in a rat model of mania has not been investigated. Crocin improves anti-oxidant activity and attenuates neuroinflammation (Shafahi et al ., 2018; Song et al ., 2022). While, inflammation has been observed in patients with mania (Dickerson et al ., 2013; Knight et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Crocin may also increase the level of neurogenesis and improves neuroplasticity (Ahmadi et al ., 2021; Tahmasebi et al ., 2022). Crocin potently decreases neuroinflammation, a mechanism involved in its’ pro-cognitive and mood enhancer effects (Scuto et al ., 2022; Song et al ., 2022). Of note, increased neuroinflammation is one of the possible underlying mechanisms of bipolar disorder and mania (Uyanik et al ., 2015; Jacoby et al ., 2016; Cyrino et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%